Ethical Decision-Making Under Uncertainty in Vector-Borne Zoonotic Disease Control: A One Health Governance Framework - Olympia Lioupi; Kornélia Kurucz; Xhelil Koleci; Pavle Banović; Dejan Jakimovski; Eleftherios Meletis; Xanthi Rousou; Gerald Barry; Gábor Kemenesi; Gustavo Monti; Polychronis Kostoulas (Zoonotic Diseases, 2026)
Decisions about vector-borne zoonotic disease control often have to be made before the evidence is complete. Human surveillance, entomological observations, animal reservoir or sentinel data, environmental indicators, and modelling outputs may provide warning before human disease patterns are clear. In some settings, early action can prevent harm, yet it can also impose social, economic, ecological, animal-welfare, liberty-related, and trust-related burdens. Technical risk assessment remains necessary, although it may need to be complemented by ethical analysis. In this conceptual manuscript, we propose a seven-step One Health ethical decision-making framework that links integrated evidence and transmission plausibility to precaution, proportionality, equity, One Health trade-offs, legitimacy, feedback, impact evaluation, and adaptation. Its contribution lies not in introducing new ethical principles, but in integrating them into an iterative governance sequence and proposing medical bioethics mediation for persistent value conflict. Illustrative domains include West Nile virus, dengue, Zika, Crimean–Congo haemorrhagic fever, and other mosquito-, tick-, and sand fly-borne zoonotic threats.